The Symphony of HRM, Ethical Climate, and Dynamic Capability in Competitive Advantage - Bilgin, Fevzullah.; Hadziahmetovic, Nereida; Tandir, Natasa; Cuong, Nguyen Manh; Kester, Ahmet; Samoylenko, Svitlana; Chelabi, Kaddour; Sateeshchandra, Navya Gubbi (Journal of Ecohumanism, 2024)
This study investigates how human resource management (HRM) practices influence competitive advantage in Nigerian private schools amidst ethical, market, and technological challenges. The research proposes that effective HRM practices — recruitment, training, compensation, and performance appraisal— foster a strong ethical climate and dynamic capability, ultimately leading to a competitive advantage (CA). Analysing data from 465 staff members of private schools in Nigeria, the findings reveal that HRM practices, notably recruitment and selection, training and development, and performance appraisal, directly impact CA. While dynamic capability influences CA, it also plays a mediating role between training and CA. This study provides quantitative evidence for the strategic value of HRM in this context, offering insights for cultivating high-performing workforces and achieving sustainable success in a competitive landscape.